Major roles of kupffer cells and macrophages in NAFLD development - Park, Soo-Jeung; Garcia Diaz, Josefina; Um, Eugene; Hahn, Young S. (Frontiers in Endocrinology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is an important public health problem with growing numbers of NAFLD patients worldwide. Pathological conditions are different in each stage of NAFLD due to various factors. Preclinical and clinical studies provide evidence for a crucial role of immune cells in NAFLD progression. Liver-resident macrophages, kupffer cells (KCs), and monocytes-derived macrophages are the key cell types involved in the progression of NAFLD, non-alcoholic steatohepatitis (NASH), and hepatocellular carcinoma (HCC). Their unique polarization contributes to the progression of NAFLD. KCs are phagocytes with self-renewal abilities and play a role in regulating and maintaining homeostasis. Upon liver damage, KCs are activated and colonized at the site of the damaged tissue. The secretion of inflammatory cytokines and chemokines by KCs play a pivotal role in initiating NAFLD pathogenesis. This review briefly describes the role of immune cells in the immune system in NAFLD, and focuses on the pathological role and molecular pathways of KCs and recruited macrophages. In addition, the relationship between macrophages and insulin resistance is described. Finally, the latest therapeutics that target KCs and macrophages are summarized for the prevention and treatment of NAFLD.